(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Based on the expedition materials received by the authors in 2014, the article reveals the cultural and psychological characteristics of the sub-ethnic group of Kryashen-pagans in the village of old Tyaberdino, the Republic of Tatarstan. The purpose of the article is to study the ethnocultural characteristics of the Kryashen pagans. The main attention in the article is paid to the traditional rituals and customs of the life cycle, and the issues of ethnic self-awareness and self-identification of “unbaptized Kryashens” are raised. The article demonstrates the way paganism and Christianity are closely intertwined in the Kryashen calendar, festive and everyday traditions, folk beliefs and customs. First of all, such a synthesis of pagan and Christian rituals is due to the geographical location of the area and interaction with neighboring peoples. Secondly, during the periods of mass Christianization, paganism was not completely ousted from the consciousness of the Kryashen people, and Christianity was not fully understood yet. The authors of the article also describe the sacred rituals and places of worship that have survived at present among the Kryashen pagans. The materials of this article can be useful for ethnologists, social and cultural anthropologists, historians, museologists and culturologists, as well as anyone interested in this topic.